2021
DOI: 10.3916/c68-2021-05
|View full text |Cite
|
Sign up to set email alerts
|

Myths in visual environmental activism narratives on Instagram

Abstract: Images are part of the communication strategies of both the hegemonic powers and political activism. Images have recently been the focus of studies on social movements, highlighting the importance of visual activism in social media. However, the relationship between these visual narratives and mythological structures and how they operate to mobilize social change has not been significantly explored. This study analyses the role of environmental activism memes on social media and how, in anthropological terms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
12
0
4
Order By: Relevance
“…This is an important indication that the webcomic through social media proposes another format in which various areas of communication can benefit to connect with potential audiences, especially those who are younger and digital. To quickly propose an example, digital media could perfectly well through a webcomic propose the explanation of news or event through this resource, in the same way, that Sidorenko et al (2021) have demonstrated with @pictoline on Instagram and the scientific message, or Ardèvol et al (2021) with environmental activism.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important indication that the webcomic through social media proposes another format in which various areas of communication can benefit to connect with potential audiences, especially those who are younger and digital. To quickly propose an example, digital media could perfectly well through a webcomic propose the explanation of news or event through this resource, in the same way, that Sidorenko et al (2021) have demonstrated with @pictoline on Instagram and the scientific message, or Ardèvol et al (2021) with environmental activism.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies looking at the discussion of environmental or energy issues on social media didn't include the images [40,41] -although especially in social networks such as Instagram-images and graphics form a vital part of the self-expression of the users [42]. Image-based platforms, such as Instagram [43], offer advantages to actors as they can support their strategic messages by selecting certain images or motifs [10].…”
Section: Images Of the Energy Transitionmentioning
confidence: 99%
“…Ross and Rivers [33] use critical discourse analysis to study how Internet memes are used to represent certain frames related to climate change. There is also a trend towards personalization in images, with frequent depictions of individuals or groups of people [40,19,16].…”
Section: Images Of the Energy Transitionmentioning
confidence: 99%
“…Treré et al (2017) compares digital protest media imaginaries, while Ristovska (2016) delves into how video activism constitutes a practice stemming from a history of visual practices mixed with political concerns. Ardèvol et al (2021) study the role of environmental activism memes in social media, highlighting the importance of visual activism, where images are part of the communication strategies. However, studies on how these visual elements operate to mobilize social change have not been significantly explored (Ardèvol et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ardèvol et al (2021) study the role of environmental activism memes in social media, highlighting the importance of visual activism, where images are part of the communication strategies. However, studies on how these visual elements operate to mobilize social change have not been significantly explored (Ardèvol et al, 2021). Indeed, Lee and Hsieh (2013) argue that online activism can lead to ‘slacktivism’ and the risk that people will superficially be active on the Internet rather than making a real difference.…”
Section: Introductionmentioning
confidence: 99%